A Review of Renewable Energy Infrastructure Trends Literature: A Case Study of Shopping Mall, Pasar Gedhe Klaten, Indonesia - Nuriana, Ari; Setiawan, Muhammad Ikhsan; Fitri, Sulidar; Laksito, Grida Saktian (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
The trajectory of literature concerning renewable energy infrastructure has evolved substantially in recent decades, reflecting the escalating significance of renewable energy sources within the broader context of the global energy scene. A noticeable shift towards integrating renewable energy infrastructure into shopping malls has emerged in recent years, marking a broader movement towards sustainability and environmental accountability within the commercial sector. Historically, shopping malls have been significant energy consumers, heavily reliant on conventional sources like fossil fuels to meet their lighting, heating, and cooling needs. Yet, escalating concerns over climate change and energy expenses have increasingly prompted mall developers and operators to adopt renewable energy solutions. By incorporating solar panels, wind turbines, and geothermal systems, shopping malls can substantially diminish their carbon footprint, reduce energy costs, and bolster their environmental standing. Furthermore, this inclination aligns with corporate social responsibility efforts, as malls strive to underscore their dedication to sustainability and attract environmentally conscious patrons. Bolstered by governmental incentives and regulatory frameworks encouraging renewable energy adoption, the trajectory of renewable energy infrastructure in shopping malls in Pasar Gedhe Klaten, Indonesia, is anticipated to persist, delivering both environmental benefits and economic gains for stakeholders.